RESEARCH OF STRUCTURAL AND MECHANICAL PROPERTIES OF MEAT AS AN OBJECT OF PROCESSING IN MEAT COMMINUTOR - KUKHTA, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
An effective work of meat comminutors is possible only on condition of consideration of properties of raw material when designing these machines. Specific properties of meat as an object of processing in comminutor is, above all, its ability to considerable deformation under external pressure. That is what leads to restricted areas of serve of meat with the screw of the comminutor to a cutting unit at every instant and, consequently, to a significant, more than 2 times, reduction of specific performance of meat comminutors. This paper presents the results of research of rheological properties of three kinds of raw meat: beef, pork and chicken, which set the module of axial compression, tension of standard penetration and tension of solid muscle tissue cutoff. The data can be used in justifying the highly productive methods of supply of meat to cutting unit of comminutors. One of the most common types of technological equipment which is used in meat-processing industry, there are meat grinder. In modern conditions the further development of these machines is subject to the general market tendencies, i.e. in the directions of increasing the specific productivity and reduce operational costs for the purchase of the cutting tool. Growth relative productivity makes it possible to increase output without increasing capital and operating costs for the maintenance of process equipment. The authors ’ analysis showing that existing designs of meat grinders available reserve of increase in productivity. Using the video for the first time the regularities of the flow rate of the raw material at the working space of lattices the cutting unit. The raw material is in every moment of time is not across the entire working area of the cutting grids of the node, but only within a certain sector, the value of which depends on the design parameters of the auger and from the structural-mechanical properties of raw materials. The supply of raw material is maximum in the zone of the approaching end of the coil auger to the cutting unit. In areas of the cutting unit, which correspond to the removal of the surface of the last turn of the screw from the suction grille, flow significantly decreases and finally completely disappears. The data obtained can be used in the justification of high-performance methods of feeding raw meat through the cutting assembly of the meat grinders, as well as in the development of more efficient and cheaper cutting tool grinders.